Integrating an early childhood development programme into Bangladeshi primary health-care services: an open-label, cluster-randomised controlled trial - Jena D Hamadani, PhD; Syeda F Mehrin, MSc; Fahmida Tofail, PhD; Mohammad I Hasan, MPH; Syed N Huda, PhD; Helen Baker-Henningham, ProfPhD; Deborah Ridout, MSc; Sally Grantham-McGregor, ProfFRCP (Elsevier, 2019)
Summary: Background: Poor development in young children in developing countries is a major problem. Child development experts are calling for interventions that aim to improve child development to be integrated into health services, but there are few robust evaluations of such programmes. Previous small Bangladeshi trials that used individual play sessions with mothers and their children (at home or in clinics), which were predominantly run by employed women, found moderate improvements on child development. We aimed to integrate an early childhood development programme into government clinics that provide primary health care and to evaluate the effects of this intervention on child cognition, language, and motor development, growth, and behaviour in a subsample of the children. Methods: In this open-label cluster-randomised controlled trial, we recruited individuals from community clinics in Narsingdi district, Bangladesh. These clinics were randomly selected from a larger sample of eligible clinics, and they were assigned (1:1) to either deliver an intervention of 25 sessions, in which mothers of eligible children were shown how to support their child's development through play and interactions, or to deliver no intervention (control group). Participants were underweight children, defined as a weight-for-age Z score of −2 SDs of the WHO standard, who were aged 5-24 months and who lived near the clinic (defined as a walk of less than 30 min). Government health workers ran these sessions at the clinics as part of their routine work, and mothers and children attended fortnightly in pairs (instead of individual weekly home visits that were specified in the original programme). A subsample of children from each clinic was randomly selected for impact evaluation, and these children were assessed on the Bayley Scales of Infant and Toddler Development for their cognitive, language, and motor performance and for their behaviour with Wolke's ratings, before and after implementation of the intervention. The primary outcomes were the performance of this evaluation subsample on the Bayley and Wolke scales and their anthropometric measurements (weight, length or height, and head circumference) after 1 year of the intervention. This study is registered with ClinicalTrials.gov, number NCT02208531. Findings: Between Nov 29, 2014, and April 30, 2015, 12 054 children in 90 clinics were screened, and between six and 25 underweight children were enrolled from each clinic. From the 2423 (20%) underweight children, we excluded 656 (27%) children who lived more than 30-min walking distance from the community clinics, and 30 (1%) children whose mothers did not consent to participate. We therefore enrolled 1737 (72%) children from these 90 clinics. After randomisation, the control group clinics included 878 (51%) children (who all received no intervention) and the intervention group clinics included 859 (49%) children (who all received the child development programme sessions). Eight children from each clinic (360 [41%] children from the control group clinics and 358 [42%] children from the intervention group clinics) were randomly selected for inclusion in the evaluation subsample. Between Feb 24, 2016, and Sept 7, 2016, 344 (96%) children in control group clinics and 343 (96%) children in intervention group clinics were assessed for the primary outcome. 16 (5%) children in the control group clinics and 15 (4%) children in the intervention group clinics did not provide all data and were not included in final analyses. An intention-to-treat analysis showed that the intervention significantly improved children's cognition (effect size 1·3 SDs, 95% CI 1·1 to 1·5; p=0·006), language (1·1 SDs, 0·9 to 1·2; p=0·01), and motor composite scores (1·2 SDs, 1·0 to 1·3; p=0·006) and behaviour ratings (ranging from 0·7 SDs, 0·5 to 0·9; p=0·02; to 1·1 SDs, 1·0 to 1·2; p=0·007), but the intervention had no significant effect on growth (p values ranged from 0·05 to 0·74). Three (1%) children in the intervention group died, but their deaths were not related to the intervention. Interpretation: The extent and range of benefits of our intervention are encouraging. Health workers ran most of the sessions effectively and attendance was good, which is promising for scale-up of the intervention model. However, researchers trained and supervised the health workers, and the next step will be to determine whether the Bangladeshi ministry of health can perform these tasks. In future programmes, more attention needs to be paid to the nutrition of the children. Funding: Grand Challenges Canada (Saving Brains).